Details that Count: Description of a Case of Pernicious Anemia - Oliveira dos Santos, Bárbara Cristina; Nogueira, Rita; Brigas, Diana; Marques, Ana (Gazeta Médica, 2023)
Pernicious anemia is an autoimmune disease associated with vitamin B12 absorption deficit. In addition of macrocytic anemia, it can cause neurological and gastrointestinal changes. Male, 76 years old, with memory loss, asthenia, dizziness, dyspnea and feeling of malaise. The analytical study carried out showed macrocytic anemia, with hemoglobin of 7.4 g/dL. The patient was referred to the emergency department, where the analytic study revealed vitamin B12 deficit, positive anti-intrinsic factor antibodies and positive anti-parietal cell antibody, confirming the diagnosis of pernicious anemia. There, he was given two units of red blood cells and he had hospital discharge medicated with intramuscular vitamin B12. After the diagnosis, the patient’s clinical history was reviewed and showed that there were complaints about memory alterations and increase of the mean of globular volume since 2015. Due to the insidious symptoms, this pathology can be underdiagnosed. This case intends to stress the importance of valuing clinical and analytical alterations, even if subtle.